Psychoeducational Assistance "Glow Up from the Inside" in Developing Positive Self-Confidence in Junior High School Students - Tsania Fitri Adenia; Lalu Muhammad Rispan Sugi Saputra (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2026)
Self-confidence is an essential component of adolescents’ psychosocial development; however, it is often misunderstood as behavior that dominates or harms others. Therefore, this community service program aimed to enhance students’ understanding and attitudes toward positive self-confidence through a psychoeducational mentoring program entitled “Glow Up from Within: Confident Without Hurting Others.” The program was conducted at SMP Islam Khadijah in October 2025 and involved all junior high school students. It applied an interactive psychoeducational approach through seminars, group discussions, and self-reflection activities. Program evaluation was conducted using multiple-choice questionnaires, Likert-scale statements, and reflective questions to assess students’ understanding and attitudes. The results showed that all students demonstrated a strong understanding of healthy self-confidence concepts. In contrast, most students showed positive attitudes in expressing opinions, demonstrating social empathy, and developing self-awareness. Students’ reflections also revealed increased confidence and a commitment to positive behavioral change. In conclusion, psychoeducational mentoring proved to be an effective approach to fostering healthy and empathetic self-confidence among junior high school students. These findings imply that similar psychoeducational programs can be implemented in schools as a strategy to support students’ socio-emotional development and promote constructive self-confidence without negatively affecting others.